(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2012)
The experiment was conducted under the agro-ecological zone of Modhupur Tract (AEZ-28) to determine the genetic diversity among 39 rice genotypes, collected from Bangladesh Rice Research Institute, Lal Teer Seed Ltd. and Chittagong Hill Tracts. The genotypes were grouped into six clusters based on Mahalanobiss D2 statistics and Canonical Variate Analysis. Cluster I consisted with the highest number of (11) genotypes from different origin, whereas cluster IV consisted with the lowest number of (3) genotypes. Cluster III consisted of BRRI dhan 28, BRRI dhan 45, Gold, Tia, Dowel and Moyna showed maximum mean yield. Maximum inter cluster distance was recorded between cluster II and cluster III. The highest inter genotypic distance was observed between Tharak dhan and BRRI dhan 45. Cluster III had the highest mean values for grain yield, harvest index, 1000-grain weight and number of effective tillers per hill and cluster V for number of primary branches per panicle and cluster VI for number of filled grains per panicle that had significant positive correlation with grain yield. Number of unfilled grains per panicle, 1000-grain weight and grain yield showed maximum contribution towards genetic divergence. The genotypes from these clusters with desirable characters may be used as potential donor for future hybridization program to develop high yielders. DOI: http://dx.doi.org/10.3329/bjpbg.v25i1.17010